How to Use PERMA Model of Positive Psychology in Occupational Therapy to Improve Well-being - Kam Man WONG; Guang ZENG (康复学报)
This article discussed about the theories on health, happiness and occupational therapy and explored their inter-relationships. Activity and participation, as key components of health, provide platform for people to pursue happiness. Daily provides chance for people to establish relationship, perceive positive emotion, engage in flow, pursue meaning, actualize self and enjoy accomplishment. These are the PERMA model on well-being and human flourishing. Occupational therapy (OT) emphasizes on the activities of daily living to restore health. The use of 3C (choice, context, celebration) theories in designing activities could help patients experience positive emotion, engagement, relationship, meaning and sense of success. This could prepare patients to pursue further health and happiness even after discharge. The OT service in mainland China is still focus more on impairment. We hope more OT services on activity, participation and PERMA could be developed.